Association of circulating miR-223 and miR-16 with disease activity in patients with early rheumatoid arthritis. Issue 10 (29th July 2013) - Filková, Mária; Aradi, Borbala; Šenolt, Ladislav; Ospelt, Caroline; Vettori, Serena; Mann, Heřman; Filer, Andrew; Raza, Karim; Buckley, Christopher D; Snow, Martyn; Vencovský, Jiří; Pavelka, Karel; et al.
Abstract : Background: Identification of parameters for early diagnosis and treatment response would be beneficial for patients with early rheumatoid arthritis (ERA) to prevent ongoing joint damage. miRNAs have features of potential biomarkers, and an altered expression of miRNAs was shown in established rheumatoid arthritis (RA). Objective: To analyse RA associated miRNAs in the sera of patients with ERA to find markers of early disease, clinical activity or predictors of disease outcome. Methods: Total RNA was isolated from whole sera in ERA patients (prior to and after 3 and 12 months of therapy with disease modifying antirheumatic drugs), in patients with established RA and in healthy controls (HC) using phenol–chloroform extraction. Expression of miR-146a, miR-155, miR-223, miR-16, miR-203, miR-132 and miR-124a was analysed by TaqMan Real Time PCR. Results: From all analysed miRNAs, levels of miR-146a, miR-155 and miR-16 were decreased in the sera of ERA patients in comparison with established RA. A change in circulating miR-16 in the first 3 months of therapy was associated with a decrease in DAS28 in long term follow-up in ERA (p=0.002). Levels of circulating miR-223 in treatment naïve ERA correlated with C reactive protein (p=0.008), DAS28 (p=0.031) and change in DAS28 after 3 months (p=0.003) and 12 months (p=0.011) of follow-up. However, neither miR-16 nor miR-223 could distinguish ERA from HC. Conclusions: Differential expression of circulating miR-146a, miR-155 and miR-16 in the sera of ERA patients may characterise an early stage of the disease. We suggest miR-223 as a marker of disease activity and miR-16 and miR-223 as possible predictors for disease outcome in ERA.